Three Selected Papers on Catalan Folklore - Emili Samper (ed.) (Publicacions Universitat Rovira i Virgili, 2014)
This volume contains a selection of three translations of articles by Josep M. Pujol (Barcelona, 1947-2012), one in each of the three areas that he defined to characterise his work in the field of folklore: the theory of interactive artistic communication; the history of folklore studies and folk literature; and folk narrative. The three articles give a taste of the important contributions he made to the study of folklore, and which have been studied and contextualised by Carme Oriol in the introduction that precedes the three texts. This edition also includes the complete folkloric bibliography of Josep M. Pujol in chronological order, with all the references.